Developing android-based interactive media in integrated science subjects for madrasah tsanawiyah students - K. Kasman; L. Lu’mu; A. Arnidah (Universitas Papua, 2026)
This study aims to develop an Android-based interactive media for valid, practical, and effective science learning. This study focuses on the development of interactive media among students of Madrasah Tsanawiyah (MTs) in Sidenreng Rappang Regency. The development process follows the AADC model, which is divided into four main stages: Analyze, Align, Design, and Construct. This research used two validators (experts in material and media), one science instructor, and 30 seventh-grade students for the trial. Data were gathered using validation sheets, questionnaires, and assessments of learning outcomes. The outcomes of the interactive media validity study during the validation phase include two dimensions: material validation and medium validation. The material validation achieved a very valid category (average 93%), whereas validation by media specialists attained a very valid category (average 90%). The evaluation findings of the individual trial response questionnaire revealed an average of 92%, while the small-group test yielded 93%, suggesting that the medium is effective for use. The teacher response questionnaire on interactive media was deemed very effective, with an average 99%. The pretest and posttest data indicated an enhancement in student learning outcomes, with an average pretest score of 51.67 and a posttest score of 86.00. The n-gain value was 0.71, indicating a substantial improvement in student learning outcomes. It may be concluded that Android-based interactive media satisfies students' demands and fulfills the criteria of validity, practicality, and effectiveness for educational purposes.